Характеристика сертифікатів евростандарту та стандарту сертифіката Х509 - Фоков, В. И. (ХНУРЭ, 2009)
Electronic digital signature can be used by any person as the hand made signature to make electronic document Law powerful . The law power of electronic document signed by Electronic digital signature is the same as the signature on the paper, signed by hand law active person or make a stamp on it.